2008
DOI: 10.1177/0269881107082481
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine aggravates symptoms of acute stress disorder in a naturalistic sample of accident victims

Abstract: The glutamatergic N-methyl-D-aspartate receptor antagonist ketamine produces transient dissociative states and alters cognitive functioning in healthy humans, thus resembling the core symptoms of acute and chronic post-traumatic stress disorder (PTSD). First evidence exists that the common use of the analgesic and sedative properties of ketamine during emergency care correlates with sustained symptoms of PTSD in accident victims. The aim of the present study was to examine whether ketamine administration after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 17 publications
1
42
0
1
Order By: Relevance
“…There have been mixed reports, for example, on the benefits of ketamine treatment received by traumatic accident and burn victims, with some reporting that it can decrease prevalence of PTSD (McGhee et al, 2008) while others report that it can increase the severity of PTSD diagnostic scores (Schonenberg et al, 2005, 2008; Winter and Irle, 2004). Tests of subanesthetic ketamine in healthy volunteers have reported dissociative and psychosis-like effects that mimic schizophrenia (Krystal et al, 1994; Morgan et al, 2004) as well as biomarkers of stress such as increased cortisol, impairment of stress-sensitive memory function, and transient changes in the activity of the hypothalamic pituitary adrenal axis revealed by brain imaging (Khalili-Mahani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There have been mixed reports, for example, on the benefits of ketamine treatment received by traumatic accident and burn victims, with some reporting that it can decrease prevalence of PTSD (McGhee et al, 2008) while others report that it can increase the severity of PTSD diagnostic scores (Schonenberg et al, 2005, 2008; Winter and Irle, 2004). Tests of subanesthetic ketamine in healthy volunteers have reported dissociative and psychosis-like effects that mimic schizophrenia (Krystal et al, 1994; Morgan et al, 2004) as well as biomarkers of stress such as increased cortisol, impairment of stress-sensitive memory function, and transient changes in the activity of the hypothalamic pituitary adrenal axis revealed by brain imaging (Khalili-Mahani et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further work by Schönenberg et al (2008) found that ketamine aggravated PTSD in burns victims, producing early acute stress disorder, dissociative states, re-experiencing, hyper arousal and avoid ance behaviours. The study looked at patients who had received a dose of either ketamine (n = 13), opioids (n = 24) or non-opioid analgesics (n = 13) during initial emergency treatment.…”
Section: Ketaminementioning
confidence: 98%
“…Two retrospective studies (Strayer & Nelson, 2008;Schönenberg, Reichwald, Domes, Badke, & Hautzinger, 2008) claim that ketamine may possibly exacerbate symptoms of PTSD. However, retrospective design in both of these studies is an A c c e p t e d M a n u s c r i p t 14 important methodological limitation.…”
Section: Some Possible Issues With the Therapeutic Use Of Ketamine Anmentioning
confidence: 99%